1976
DOI: 10.2136/sssaj1976.03615995004000050019x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ionic Strength and Inorganic Complex Formation on the Sorption of Trace Amounts of Cd by Montmorillonite

Abstract: Cadmium sorption by montmorillonite from solutions in the 15 to 120 ppb range was studied in the presence of increasing concentrations of NaClO4, NaCl, and Na2SO4 solutions. The ionic strengths ranged from 0.01 to 1.00. Increasing ionic strengths decreased the amount of Cd sorbed on the clay surfaces. The percentage sorbed decreased from around 90% for I = 0.01 to about 50% for I = 1.00 in the ClO4 systems. The sorption of Cd in the chloride system was in the range between 25 to 50% less than the ClO4 systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
6

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(58 citation statements)
references
References 0 publications
4
48
0
6
Order By: Relevance
“…The Cl -1 complexes of Cd are negatively or neutrally charged and therefore reduce Cd sorption on cation exchange sites. Thus, under relatively high Cl concentrations, as may occur with some saline soils, the solubility and mobility of Cd may be increased substantially, although reduced sorption was also observed at Cl concentrations representative of those commonly found in soil solutions (Garcia-Miragaya and Page 1976). Increasing chloro-complexation would increase diffusion of Cd to the root surface, thereby increasing phytoavailability (McLaughlin et al 1994).…”
Section: Soil Factorsmentioning
confidence: 96%
See 2 more Smart Citations
“…The Cl -1 complexes of Cd are negatively or neutrally charged and therefore reduce Cd sorption on cation exchange sites. Thus, under relatively high Cl concentrations, as may occur with some saline soils, the solubility and mobility of Cd may be increased substantially, although reduced sorption was also observed at Cl concentrations representative of those commonly found in soil solutions (Garcia-Miragaya and Page 1976). Increasing chloro-complexation would increase diffusion of Cd to the root surface, thereby increasing phytoavailability (McLaughlin et al 1994).…”
Section: Soil Factorsmentioning
confidence: 96%
“…Increases in ionic strength also increased the concentration of Cd in the soil solution (Petruzzelli et al 1985;Lorenz et al 1994). Garcia-Miragaya and Page (1976) suggested that the decrease in Cd sorption with increasing ionic strength of an electrolyte was due to: (i) competition of Cd 2+ with the electrolyte cations for available clay surface sites; (ii) decreased activity of the Cd 2+ in solution and; (iii) formation of uncharged ion pairs and/or uncharged and negatively charged complexes of Cd with the anions in the electrolyte.…”
Section: Soil Factorsmentioning
confidence: 96%
See 1 more Smart Citation
“…Adsorption isotherms describe the relationship between the mass of the adsorbed substance (adsorvate) by the solid (adsorvent) and the concentration of the substance in the solution in equilibrium. One of the models used to describe the adsorption of elements is the Freundlich equation: x/m = KC n , in which x = mass of the element adsorbed; m = mass of the adsorvent solid phase; C = concentration of the equilibrium of the adsorvate in solution and K and n are empirically determined constants (Garcia-Miragaya and Page, 1976;Bowman et al, 1981). Another model used to describe metal adsorption is the Langmuir equation.…”
Section: Introductionmentioning
confidence: 99%
“…Soils from Baotou and Beijing had pH values ≥ 7.8 or 8.4 (measured in deionized water without CO 2 ) and the impact of leaching is likely to be because of the effects of high ionic strength and higher concentrations of other competing cations (e.g., Ca, Mg and Na). The competing cations reduce Pb partitioning in unleached treatment soils and therefore influence Pb toxicity (Garcia-Miragaya and Page, 1976;Mattigod et al, 1979;Zhu and Alva, 1993). High ionic strength reduces Pb sorption (Puls et al, 1991) and free metal ion activity in solution (Zhu and Alva, 1993).…”
Section: Influence Of Soil Leaching On Pb Toxicitymentioning
confidence: 99%